Kinerja Reproduksi Induk Sapi Silangan Simmental Peranakan Ongole dan Sapi Peranakan Ongole Periode Postpartum - Wisnu Tri Husodo Michael Christoffor; Endang Baliarti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2008)
Aim of this study was to find out the reproduction performance of Simmental Ongole crossbred (SIMPO) and Ongole crossbred (PO) cows from parturition to four months after parturition in farming system Bambanglipuro district, Bantul sub-province.  Using 18 SIMPO and 20 PO cows as nine months of pregnancy condition. The variables observed were cows body weight, score perinatal,  postpartum anestrus (PPA), service per conception (S/C), conception rate (CR), calving interval (CI). The data on gain weight of the cows, body weight at parturition, length of pregnancy, PPA, S/C and CI were analyzed using t test while CR were analyzed using Chi-Square. The result of the study showed that SIMPO body weight at parturion was higher (P<0.01) than PO (463.70 ± 47.29 kg vs 349.90 ± 63.34 kg). Cows body weight from parturition to four months after parturition of SIMPO was higher (P<0,01) than PO but Average Daily Gain in first and second months after parturition SIMPO have more decreased (P<0,01) than PO, but in third and fourth months did not differ significantly. Length of gestation, PPA, CI, S/C and CR did not differ significantly.. The conclusion of this study was the performance of SIMPO better than PO in the case of body weight but not different in reproduction status.  Key words : Performance, Simmental Ongole crossbred, Ongole crossbred, Postpartum